In vitro Alpha Lipoic Acid supplementation in freeze-dried human sperm: the impact on DNA fragmentation index - Rezia Octarina; M. P. B. Dyah Pramesti; Agustinus Agustinus (Universitas Muhammadiyah Surabaya, 2021)
Freeze-drying technique is an alternative method on sperm preservation. However, this process can results in DNA damage. Adding antioxidants before freezing can reduce the detrimental effects of ROS on spermatozoa. Alpha lipoic acid (ALA) is one of the potent antioxidant that can be used to protect the sperm DNA. This study was aimed to determine the effect of ALA supplementation before freeze-drying on the DNA fragmentation index (DFI) of human spermatozoa. Nine semen samples were collected and evaluated for DFI (O1) then divided into 3 groups; freeze-drying without ALA (O2), freeze-drying with ALA 1,25 mg (O3) and freeze-drying with ALA 2,5 mg (O4).All three groups were stored at 4oC for 1 week. Sperm DFI were evaluated before and after freeze-drying. The result of this study showed a significant increase in sperm DFI in all three groups after freeze-drying (p<0,05) when compared to DFI before freeze-drying (14,67 ±3,295). However there was no significant difference between O2 (26,90 ±9,180) and O4 (29,29 ±5,524) group where the supplementation of 2,5 mg ALA did not have significant effect on protecting the DNA of freeze-dried human spermatozoa. The highest DFI was in the O3 group (44,64 ±11,717). Therefore, ALA supplementation before freeze-drying does not have a significant effect on protecting the DNA of freeze-dried human spermatozoa.